Shared Mechanisms for Mutually Exclusive Expression and Antigenic Variation by Protozoan Parasites - Florini, Francesca; Visone, Joseph E.; Deitsch, Kirk W. (Frontiers in Cell and Developmental Biology, 2022)
Cellular decision-making at the level of gene expression is a key process in the development and evolution of every organism. Variations in gene expression can lead to phenotypic diversity and the development of subpopulations with adaptive advantages. A prime example is the mutually exclusive activation of a single gene from within a multicopy gene family. In mammals, this ranges from the activation of one of the two immunoglobulin (Ig) alleles to the choice in olfactory sensory neurons of a single odorant receptor (OR) gene from a family of more than 1,000. Similarly, in parasites like Trypanosoma brucei, Giardia lamblia or Plasmodium falciparum, the process of antigenic variation required to escape recognition by the host immune system involves the monoallelic expression of vsg, vsp or var genes, respectively. Despite the importance of this process, understanding how this choice is made remains an enigma. The development of powerful techniques such as single cell RNA-seq and Hi-C has provided new insights into the mechanisms these different systems employ to achieve monoallelic gene expression. Studies utilizing these techniques have shown how the complex interplay between nuclear architecture, physical interactions between chromosomes and different chromatin states lead to single allele expression. Additionally, in several instances it has been observed that high-level expression of a single gene is preceded by a transient state where multiple genes are expressed at a low level. In this review, we will describe and compare the different strategies that organisms have evolved to choose one gene from within a large family and how parasites employ this strategy to ensure survival within their hosts.